Analisis Komprehensif pada Implementasi Pembelajaran dengan Model Inkuiri Terbimbing: Aspek Penalaran Ilmiah - Erni Yulianti; Nailah Nur Zhafirah (Jurnal Penelitian Pendidikan IPA, 2020)
In this study, students’ scientific reasoning ability was set as the main indicator to measure the learning achievement via guided inquiry. The research was based on mixing two analitycal techniques using quantitative and qualitative data. The pre/post-test scores were used as the quantitative data to evaluate the students’ reasoning abilities. The comprehensive statistical analyses were done to evaluate (1) the difference level of the pre/post-test scores using paired t-test, (2) the increase level of the test score by calculating the N-gain, and (3) the effectivity of the learning model realization on the increased score through the d-effect size analysis. Indeed, those statistical analyses were executed after the pre/post-test scores were normally distributed and in accepted skewness interval. The experimental results, involving 24 junior high school students, showed that the calculated t value was 11.63 higher than that of the score in the t-table. Meanwhile, the N-gain value and the d-effect size 0.8 (upper medium level) and 3.56 (very high category), respectively. Thus, the guided inquiry model provided significant effect on the increase in students’ test scores in measuring their scientific reasoning abilities. In addition, the qualitative observation indicated that the learning model was well implemented